DC Electric Field Dependence of the Dielectric Constant of Pzt Thin Films Prepared by Polymeric Precursor Method - Araujo, E. B. [UNESP]; Eiras, J. A. (Taylor & Francis Ltd, 2008)
This work reports dielectric measurements performed on Pb(Zr0.53Ti0.47)O3 (PZT) thin films prepared by a polymeric precursor method. The -E curves obtained for the PZT film measured at 100 kHz, under a small ac 0.2 kV/cm signal-test and a dc scan featured a typical butterfly curve. However, the -E curves obtained for PZT film under a dc scan, with a scan rate of 0.003 V/s, shows a pronounced asymmetry. The absence of a symmetric secondary peak in -E curves could be an indication of essentially 180 domain switching.